2010
DOI: 10.1109/tbme.2009.2036000
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Telemonitoring of Parkinson's Disease Progression by Noninvasive Speech Tests

Abstract: Abstract-Tracking Parkinson's disease (PD) symptom progression often uses the Unified Parkinson's DiseaseRating Scale (UPDRS), which requires the patient's presence in clinic, and time-consuming physical examinations by trained medical staff. Thus, symptom monitoring is costly and logistically inconvenient for patient and clinical staff alike, also hindering recruitment for future large-scale clinical trials. Here, for the first time, we demonstrate rapid, remote replication of UPDRS assessment with clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
288
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(307 citation statements)
references
References 32 publications
6
288
0
13
Order By: Relevance
“…21,22 Instead, few results were obtained for the automation of exercises that involve facial muscles like those commonly performed in speech therapy protocols. The main reasons are related to the high costs of the methods used to study articulatory movements.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Instead, few results were obtained for the automation of exercises that involve facial muscles like those commonly performed in speech therapy protocols. The main reasons are related to the high costs of the methods used to study articulatory movements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific pattern of the development of speech symptoms with disease progression is still unknown. Recent work in the field has indicated that acoustic measures of speech production can be highly predictive of patient function (e.g., Little et al, 2009;Tsanas et al, 2010). Our long-term goal is to identify a set of acoustic parameters that can be used as a biomarker for PD progression.…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, it is possible to achieve classification rates of up to 91.4%. Additionally, in [6] the evolution of the PD through the time is studied using a set of features composed by different dysphonia measures (including some from NLD) and analyze their correlation with the evolution of the patients according to the Unified Parkinson Disease Rating Scale (UPDRS) [7] in a period of six months. The authors stated that UPDRS scale can be mapped with a precision of up to 6 points.…”
Section: Introductionmentioning
confidence: 99%